2014
DOI: 10.3109/09537104.2014.974527
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma miR-223 and platelet reactivity in patients with coronary artery disease on dual antiplatelet therapy: A preliminary report

Abstract: Decreased plasma levels of microRNA-223 (miR-223), predominantly of platelet origin, were proposed as a surrogate marker of efficacy of antiplatelet therapy. However, higher on-treatment platelet reactivity was associated with lower plasma miR-223 in patients with coronary artery disease (CAD) on dual antiplatelet therapy (DAPT) including clopidogrel and aspirin. Our aim was to compare plasma miR-223 and platelet reactivity in CAD patients on DAPT with newer P2Y12 antagonists vs. clopidogrel. We studied 21 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 24 publications
(51 reference statements)
3
84
3
Order By: Relevance
“…Because studies showed that circulating miRNAs often bind to carrier proteins or are wrapped in exosomes, they may be better protected from RNase and serve as better endogenous controls. miR-16 has been used in a variety of studies, such as studies on gastric cancer [45], adrenocortical tumors [46] and coronary artery disease [47].…”
Section: • Endogenous Controlmentioning
confidence: 99%
“…Because studies showed that circulating miRNAs often bind to carrier proteins or are wrapped in exosomes, they may be better protected from RNase and serve as better endogenous controls. miR-16 has been used in a variety of studies, such as studies on gastric cancer [45], adrenocortical tumors [46] and coronary artery disease [47].…”
Section: • Endogenous Controlmentioning
confidence: 99%
“…Notably, one analysis showed that when patients treated with antiplatelet therapy were dichotomized according to a platelet response assay, miRNA-223 levels were significantly lower in patients in the Blow response^group compared to those with a Bnormal response,^a difference which was independent of other variables including CYP2C19 loss-of-function genotypes [78]. In addition, miRNA-223 was found to be further decreased in patients treated with the more potent P2Y12 inhibitors, prasugrel and ticagrelor, when compared to clopidogrel [80], which may be a surrogate for the differences in treatment effects seen between these drugs in randomized control trials [81].…”
Section: Evaluating Response To Standard MI Treatmentmentioning
confidence: 95%
“…[38][39][40] In addition, some miRNAs are closely related to platelet function, their responsiveness to antiplatelet treatment, and, hence, to stent thrombosis. 94 Therefore, this represents an active area of research as discussed in the next paragraphs.…”
Section: Platelets Mirnas Are Involved In Vascular Injurymentioning
confidence: 99%
“…[116][117][118] The large clinical potential of platelet-derived miRNAs is well exemplified by the evidence that low plasma levels of miR-223 are a reliable marker of platelet responsiveness to antiplatelet therapy, a key issue in stent thrombosis. 94 Besides circulating platelet-derived miRNAs, these molecules can be also easily measured from platelet pellets. Interestingly, elevated levels of miR-340 and miR-624 were found in platelets from young patients with early development of coronary artery disease as compared with healthy controls.…”
Section: Circulating Mirnas As Biomarkers After Coronary Angioplastymentioning
confidence: 99%